(untitled) (Journal SCIENCEVOLUTION, 2025)
The purpose of this research is to analyze the relationship between Brand Love, Innovation, Electronic Word-of-Mouth (e-WOM), and Purchase Intention in the dairy beverage sector in the city of Machala. A quantitative approach was employed, with a non-experimental, cross-sectional, and correlational design. The sample consisted of 330 individuals aged 18 to 45, selected through convenience sampling. Data analysis was conducted using partial least squares structural equation modeling (PLS-SEM) via SmartPLS software. The results revealed that Brand Love positively influences Purchase Intention, the perception of Innovation, and the willingness to recommend the brand. Additionally, Innovation was found to have a direct effect on Purchase Intention. However, e-WOM did not exhibit a significant relationship with Purchase Intention, suggesting it does not always directly influence consumer decisions. It is concluded that emotions play a fundamental role in consumption decisions. Companies that emotionally connect with customers, innovate, and communicate with closeness achieve success in the current market. This study provides a practical and useful guide for brands seeking to position themselves in the local environment.